2014
DOI: 10.1002/2013jb010867
|View full text |Cite
|
Sign up to set email alerts
|

Systematic survey of high‐resolutionbvalue imaging along Californian faults: Inference on asperities

Abstract: Understanding and forecasting earthquake occurrences is presumably linked to understanding the stress distribution in the Earth's crust. This cannot be measured instrumentally with useful coverage. However, the size distribution of earthquakes, quantified by the Gutenberg‐Richter b value, is possibly a proxy to differential stress conditions and could therewith act as a crude stress‐meter wherever seismicity is observed. In this study, we improve the methodology of b value imaging for application to a high‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0
15

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 86 publications
5
118
0
15
Order By: Relevance
“…Schorlemmer et al (2005) examined the b values of earthquakes in different stress regimes and found that lower values correlated with areas of higher differential stress. Similar trends have been reported for induced seismicity (Bachmann et al, 2012) but also in tectonic earthquakes (Tormann et al, 2014(Tormann et al, , 2015Spada et al, 2013) and laboratory experiments (Amitrano, 2012;Goebel et al, 2012). Thus, it was hypothesized that b values are related to local stress conditions (Scholz, 2015), or -in the context of induced earthquakes -to a combination of pressure and stress conditions.…”
Section: Induced Seismicitysupporting
confidence: 66%
“…Schorlemmer et al (2005) examined the b values of earthquakes in different stress regimes and found that lower values correlated with areas of higher differential stress. Similar trends have been reported for induced seismicity (Bachmann et al, 2012) but also in tectonic earthquakes (Tormann et al, 2014(Tormann et al, , 2015Spada et al, 2013) and laboratory experiments (Amitrano, 2012;Goebel et al, 2012). Thus, it was hypothesized that b values are related to local stress conditions (Scholz, 2015), or -in the context of induced earthquakes -to a combination of pressure and stress conditions.…”
Section: Induced Seismicitysupporting
confidence: 66%
“…Indeed, the correlation between b-value and stress as observed in laboratory experiments 3,4 , and indicated by this and previous seismicity studies 6-8 , is not unique: what drives the increase of the relative frequency of large events in a particular area-that is, the likelihood that small asperities preferably break together, rather than one by one 7,15 ? Whereas the stress level is an intuitive key parameter, other different factors have been suggested to play a role, such as the degree of material heterogeneity 31 , or the degree of stress concentration (proportional to the product of stress and the square root of the length of the nucleating fracture) 32 .…”
Section: Potentially Underlying Physical Processesmentioning
confidence: 53%
“…Such high rates of microseismicity are commonly observed in creeping faults [Scholz, 1990;Malservisi et al, 2005], where strain is accumulated in the transition zone from locked to creeping patches [Vidale et al, 1994;Nadeau et al, 1995;Sammis and Rice, 2001;Waldhauser and Ellsworth, 2002]. However, these statistical relationships vary by style of faulting, tectonic loading rate, and aseismic slip behavior [Amelung and King, 1997;Wyss et al, 2004;Schorlemmer et al, 2005;Tormann et al, 2014]. The predominantly high b value (>1.2) and D~2b have been proposed as more suitable descriptors of the creeping portion of the fault [Wyss et al, 2004].…”
Section: Resultsmentioning
confidence: 99%